Complexity of intestate estates distribution and escheat law - Mohammada, Mohammad Tahir Sabit; Suratman, Robiah (Global Academic Excellence, 2017)
Previous works have discussed the jurisdictional aspects of administration of intestate estates of Muslims in Malaysia. This paper adds to the literature by showing the complexities of the current legal framework that may have caused slow distribution and determination of escheatable estates. The objectives of the paper include the examination of the existing law on reporting, claiming, and administration of estates as well as the effectiveness and adequacy of them. For this, relevant legislations are examined. The analysis of these legislations showed a number of complexities in subject areas. The paper is a preliminary work that needs validation. The authors suggest further research for a validated conceptual framework.